Performance and Quality of Artificial Rice Made from Red Bean Flour (Phaseolus vulgararis L.) and Various Types of Bulb Flour - Tri Ida Mulyani; Ida Agustini Saidi (Nabatia, 2015)
This study was to determine the proportion effect of different types of tubers flour and red beans (Phaseolus vulgaris L.) on the quality of artificial rice. The experiment was arranged in a randomized block design (RBD) with treatment consisting mixture of cassava flour: red bean flour, sweet potato flour: red bean flour, cocoyam flour: red bean flour with composition of 100%: 0%, 85%: 15% and 70%: 30%, as well as paddy rice IR 64 as a control; with triplicate experiments then obtained 30 experimental unit. Measured variables were chemical analysis (amylose content and protein content), physical analysis (cooked rice, volume expansion and power rehydration) and organoleptic (color, aroma,flavor and texture). Data were analyzed using ANOVA, followed by testing HSD 5%,while the organoleptic test was analyzed using Friedman test. The results showed significantlydifferent on the amylose content, volume expansion and power rehydration of rice; organoleptic test result showed significantly different between treatment of color, aroma and texture;and notsignificantly different on taste. Overall assessment, the IR rice has a higher value than the artificial rice, but the artificial rice with cassava flour without the addition of red bean flour has the best score compared to other artificial rice.